PERANAN JAKSA TERKAIT ASAS DOMINUS LITIS BERDASARKAN SISTEM PERADILAN PIDANA DI INDONESIA - Johannes Pasaribu; Alvi Syahrin; Muhammad Ekaputra; Suhaidi Suhaidi (USU LAW JOURNAL, 2018)
ABSTRACT   The existence of the authority of prosecutors in Indonesia in prosecution is closely related to the principle of dominus litis. In accordance with the principle of dominus litis, the determination and control of prosecution policy is only in one hand, namely the prosecutor's office. Prosecutors conduct investigations only in connection with certain crimes. This leads to the need to review the authority of the prosecutor on the investigation and prosecution in the Indonesian Criminal Justice System linked to the dominus litis principle. Regarding the formulation of the regulation of the authority of the prosecutor at the stage of investigation and prosecution as an attempt to renew the criminal procedure law in Indonesia is associated with the dominus litis principle.   Keywords: Prosecutor, Dominus Litis, And Prosecution